2020
DOI: 10.1016/j.joca.2020.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Patients', healthcare providers', and insurance company employees' preferences for knee and hip osteoarthritis care: a discrete choice experiment

Abstract: Objective: To determine patients', healthcare providers', and insurance company employees' preferences for knee and hip osteoarthritis (KHOA) care. Design: In a discrete choice experiment, patients with KHOA or a joint replacement, healthcare providers, and insurance company employees were repetitively asked to choose between KHOA care alternatives that differed in six attributes: waiting times, out of pocket costs, travel distance, involved healthcare providers, duration of consultation, and access to special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…12,13 A discrete choice model found evaluating patient and provider priorities found that both populations valued low out-of-pocket costs the most when deciding where to obtain/administer care for knee or hip osteoarthritis. 14 Dekhne et al 1 reviewed a database of 216,263 collective arthroscopic meniscal repair, lumbar discectomy, total knee arthroplasty, and total hip arthroplasty patients and demonstrated that 1 in 6 patients are at risk for a surprise bill despite seeking care at an in-network facility. Patients undergoing lumbar discectomy were particularly susceptible, whereby 24.5% received a surprise bill, most commonly from an intraoperative neuromonitoring company.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 A discrete choice model found evaluating patient and provider priorities found that both populations valued low out-of-pocket costs the most when deciding where to obtain/administer care for knee or hip osteoarthritis. 14 Dekhne et al 1 reviewed a database of 216,263 collective arthroscopic meniscal repair, lumbar discectomy, total knee arthroplasty, and total hip arthroplasty patients and demonstrated that 1 in 6 patients are at risk for a surprise bill despite seeking care at an in-network facility. Patients undergoing lumbar discectomy were particularly susceptible, whereby 24.5% received a surprise bill, most commonly from an intraoperative neuromonitoring company.…”
Section: Discussionmentioning
confidence: 99%
“…A previous ESCEO DCE of patients with hip and knee osteoarthritis showed that the most important treatment attributes were impact on disease progression followed by the ability to improve walking and reduce pain [ 23 ]. In another US DCE study, including hip and knee osteoarthritis patients, healthcare providers and insurance company employees, the most important attribute was out of pocket costs [ 24 ] (though it should be noted that this was not included as an attribute in the ESCEO study and might be related to the US healthcare distribution system). Another DCE in the US included patients with osteoarthritis and chronic low back pain and found a preference for daily oral medication over longer term intravenous therapy [ 25 ].…”
Section: Patient Preferences and Shared Decision-makingmentioning
confidence: 99%
“…An overview of the case studies and their DCE designs can be found in Table 1. [30][31][32] Attributes and levels were selected based on literature reviews, focus groups, and interviews; these are presented in Table 2. The first case study concerned the treatment preferences of patients with multiple sclerosis (MS) in The Netherlands, France, and the UK.…”
Section: Case Studiesmentioning
confidence: 99%
“…The third study concerned care for hip and knee osteoarthritis (HKOA) in The Netherlands. 32 Respondents aged 45 years and older with knee or hip osteoarthritis were recruited online, also via Dynata (N = 648). In contrast to the other 2 studies, none of the attributes were explicitly described to respondents as being related to risks.…”
Section: Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation